Smart Vertical Farming: The Role of IoT in Achieving Sustainability and Resource Efficiency - Ayu Citra Setiawan, Putu; Indra ER, Ngurah; Sukadarmika, Gede (Majalah Ilmiah Teknologi Elektro, 2025)
The rapid growth of population and ongoing urbanization have posed significant challenges to global food production systems. With more than half of the world's population now residing in urban areas, this figure is projected to rise to 70% in the coming decades. The conversion of agricultural land into residential and infrastructure zones has reduced local food production capacity, increasing reliance on food supplies from outside urban areas. Additionally, climate change exacerbates these challenges through weather fluctuations that affect agricultural yields in rural regions. Vertical farming has emerged as an innovative solution, offering an environmentally friendly approach to meet the growing food demand. Vertical farming systems enable the year-round production of high-quality crops with fully automated environmental controls powered by Internet of Things (IoT) technologies. Using sensors and artificial intelligence, vertical farming can monitor and adjust growth factors such as temperature, humidity, and lighting in real time. This study aims to explore the contributions of smart vertical farming in achieving sustainability and resource efficiency by analyzing resource utilization, environmental sustainability, and economic and social impacts. The research seeks to provide insights into the potential of vertical farming as a scalable, self-sustaining mechanism to support urban food security. The findings are expected to contribute significantly to the development of more environmentally friendly and sustainable agricultural practices in the future.